Shrimps (Crustacea, Decapoda, Caridea) associated with gorgonians at the coast of Senegal - Wirtz, Peter (2020)
Symbioses are common in the marine environment. Some taxa appear to be particularly prone to be involved in associations. Crustaceans probably form more associations with other classes than any other marine animals (Ross 1983), crustacean – cnidarian associations being particularly common (Patton 1967). Gorgonianassociated decapods have been described from both sides of the Atlantic (e.g. Spotte et al. 1994, 1995, Wirtz & d´Udekem d´Acoz 2001, Wirtz et al. 2009). Gorgonians were therefore searched for associated decapods during three dives in the area of NGor, Senegal, i.e. at the western tip of Africa.